2013
DOI: 10.1002/ajpa.22425
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for long‐term migration on the Balkan Peninsula using dental and cranial nonmetric data: Early interaction between Corinth (Greece) and its colony at Apollonia (Albania)

Abstract: This article seeks to identify "Greeks" and "non-Greeks" in "mixed" mortuary contexts in a Greek colony. Specifically, we test the hypothesis that Illyrian and Greek individuals lived and were buried together at the Corinthian colony of Apollonia, Albania (established ca. 600 BC). The pattern of human biological interaction at Apollonia is tested by identifying variation in genetic relatedness using biodistance analysis of dental and cranial nonmetric traits for three sites: Apollonia (n = 116), its founder-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Interestingly, a modern DNA study revealed that there is indeed a Greek genetic signature in southern Italian present‐day populations that can, by modelling the typical mutation rate over the centuries, be attributed to a migration influx somewhere between the eighth and fifth century bc (Tofanelli et al ., ). We hope that future comparative work on bioarchaeological data from the supposed mother cities in Greece will bring us closer to understand the timing and degree of Greek‐indigenous admixture at Metaponto (for example, McIlvaine et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a modern DNA study revealed that there is indeed a Greek genetic signature in southern Italian present‐day populations that can, by modelling the typical mutation rate over the centuries, be attributed to a migration influx somewhere between the eighth and fifth century bc (Tofanelli et al ., ). We hope that future comparative work on bioarchaeological data from the supposed mother cities in Greece will bring us closer to understand the timing and degree of Greek‐indigenous admixture at Metaponto (for example, McIlvaine et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, large‐scale biological investigations, which could provide crucial information regarding migration and admixture, remain rare (with a few recent exceptions, e.g. McIlvaine et al ., ; Tofanelli et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have proposed methods that address the probable violation of the stationarity assumption in past populations, such as using models that allow for the estimation of population growth rates or using proxies for birth rates based on the proportions of subadults in skeletal samples Buikstra et al 1986;Kohler and Reese 2014;White 2014;Wood et al 2002). Archaeological research is also addressing migration and population growth (or decline) through isotope analysis (e.g., Beaumont et al 2013;Keenleyside et al 2011;Knudson et al 2012), ancient DNA studies (e.g., Li et al 2011;O'Fallon and Fehren-Schmitz 2011;Raff et al 2011), biodistance analysis (e.g., McIlvaine et al 2014;Torres-Rouff et al 2013), and GIS-based analyses of settlement patterns and trends in population size (Jones 2010(Jones , 2014. Although demographic nonstationarity remains an important issue for bioarchaeologists, our primary focus here, following Wood et al (1992), is on heterogeneous frailty and selective mortality, both of which affect ancient health research more directly.…”
Section: The Osteological Paradoxmentioning
confidence: 99%
“…Although there were consistently high rates of platymeria throughout Albania suggesting that ancestral Albanians exhibited subtrochanteric flattening (Table 2), the temporal changes in platymeria documented here may be complicated by population movements and gene flow in the region through time. McIlvaine et al (2014) found that the majority of individuals from Prehistoric through Hellenistic periods at Apollonia represent local Illyrians, but Schepartz (2010 documented significant variation in cranial morphology between the Prehistoric and Post-Medieval/Modern inhabitants of both Apollonia and Lofkënd, indicating that the Post-Medieval/Modern peoples may have been a product of the European trend toward brachycephalization (Dhima, 1993;Nemeskéri and Dhima, 1988), or substantial gene flow in the region. Several waves of colonization (i.e., the Greeks, Romans, and Ottomans) and substantial migration throughout the region suggest that the earlier Albanian (Illyrian) populations were not the only contributors to the modern Albanian gene pool.…”
Section: Migration and Gene Flowmentioning
confidence: 99%